Bayi Berat Lahir Rendah (BBLR) di Provinsi Jawa Timur Tahun 2012-2016 - Indri Hartiningrum; Nurul Fitriyah (Universitas Airlangga, 2018)
LBW classified as one of children health problems in Indonesia which impacts Infant Mortality Rate (IMR). According to Riskesdas 2010, LBW in Indonesia was noted approximately 11,1%, while in East Java was noted approximately 10,1%. This study aims for knowing a pattern of LBW on the 5 years latest in the East Java since that LBW is regarded as the public health indicator because it affects bigger for the children’s life in further. This study was descriptive research within quantitative approach using the secondary source from Health Profile of East Java Province during 2012 until 2016. Based on this method, city has a large number of LBW patience are Madiun (8.6%), Situbondo (5%) and Bondowoso (4.6%). Pattern of LBW cases in East Java were fluctuative and did not change to better yet. In conclusion, 3 cities who have the high percentage number of LBW was caused an illness during the women’s pregnant and the lack of knowledge about the nutrition proposition. It showed that the program who done by the government for decreasing the number of LBW in East Java was not efficient yet, so, it is needed an intervention in advance.